GLYT1 encephalopathy: Further delineation of disease phenotype and discussion of pathophysiological mechanisms. Issue 2 (2nd December 2020) - Mademont‐Soler, Irene; Casellas‐Vidal, Dolors; Trujillo, Alberto; Espuña‐Capote, Núria; Maroto, Anna; García‐González, Maria del Mar; Ruiz, María Dolores; Diego‐Álvarez, Dan; Queralt, Xavier; Perapoch, Josep; Obón, María
Abstract: GLYT1 encephalopathy is a form of glycine encephalopathy caused by disturbance of glycine transport. The phenotypic spectrum of the disease has not yet been completely described, as only four unrelated families with the disorder have been reported to date. Common features of affected patients include neonatal hypotonia, respiratory failure, encephalopathy, myoclonic jerks, dysmorphic features, and musculoeskeletal anomalies. All reported affected patients harbor biallelic genetic variants in SLC6A9 . SNP array together with Sanger sequencing were performed in a newborn with arthrogryposis and severe neurological impairment. The novel genetic variant c.997delC in SLC6A9 was detected in homozygous state in the patient. At protein level, the predicted change is p.(Arg333Alafs*3), which most probably results in a loss of protein function. The variant cosegregated with the disease in the family. A subsequent pregnancy with ultrasound anomalies was also affected. The proband presented the core phenotypic features of GLYT1 encephalopathy, but also a burst suppression pattern on the electroencephalogram, a clinical feature not previously associated with the disorder. Our results suggest that the appearance of this pattern correlates with higher cerebrospinal fluid glycine levels and cerebrospinal fluid/plasma glycine ratios. A detailed discussion on the possible pathophysiological mechanisms of the disorder is also provided.